Managing the self: a grounded theory study of the identity development of 14-19 year old same-sex attracted teenagers in British Schools and Colleges - Jones, Roger (2012)
The process of Lesbian, Gay or Bisexual (LGB) identity formation is a complex one. There are many barriers in place which, implicitly or otherwise, seek to control and regulate same-sex attraction. An essential part of LGB identity formation is the process of disclosure to others, which can elicit a variety of reactions, from instant rejection to intense camaraderie. An examination of the ways in which LGB teenagers manage the visibility of their sexual identities, in the face of heterosexual control and regulation, will have profound implications for the work of those professionals who work with these young people. Using a Constructivist Grounded Theory approach (Charmaz 2005, 2006), this study examines the experiences of 14-19 year old LGB teenagers concerning self-discovery, disclosure to others, coping with negative pressures and school responses to LGB visibility. Students, teachers and school managers were asked about the promotion of heterosexual and LGB-friendly assumptions and values in a school context. Thirty-five LGB young people were asked about how these assumptions had affected their lives. Some participants seemed able to manage anti-LGB pressures much better than others and, in order to determine why, participants were asked to identify the social, verbal and non-verbal strategies they have adopted in order to manage their LGB visibility in the face of these pressures. The emergent theory is entitled ‘A Constructivist model of LGB youth identity development’. By focusing on self-presentation and the management of homonegative pressures, this study highlights the need for a greater awareness of the ways in which LGB teenagers cope with social stigmatisation and manage disclosure in order to gauge the likely reactions from others. By developing an awareness of LGB visibility management, it will be possible for those who work with young LGB teenagers to circumvent some of the adverse interpersonal and psychological effects of homonegative stigmatisation